Studying the Reality of Performance Affectivity in Some Bureaus of Ministry of Youth and Sports from The Administrative Bureau Members’ Point of View for Active Clubs in Baghdad - Abbas, Rasha; Mohsen, Noha (Journal of Physical Education, 2023)
The study aimed identifying the reality of performance affectivity in some bureaus of Ministry of youth and sports. The researchers used the descriptive method on (385) members of the administrative sport clubs’ bureaus from sport clubs. They constructed a scale of five fields and thirty-two items for measuring contradictions in ministry of youth and sport bureaus from the active administrative member’s point of view in Baghdad. The researchers concluded that the scale have a great importance as a scientific means for detecting the level of affectivity. The results also showed that members of some ministry of youth and sports bureaus have a good level in contradiction administration and tension control from the administrative bureau’s point of view. The researchers recommended giving ministry employees the freedom to act within their jurisdiction to facilitate work and overcome tension and negative contradictions so as to develop the level of affectivity of administrative work.